Access in the Food Environment: A Health Equity Approach Reveals Unequal Opportunity. (March 2020) - Diehl, Jessica A.; Heard, Debbie; Lockhart, Steven; Main, Deborah S.
Evidence shows that not all places offer people equal access to affordable, healthy food; unequal access is a potential explanation for disparities in health. This study applied the theoretically grounded social science concept of health equity to shift the focus from equal (same for all) to equitable (needs-based) access. Using data from Taking Neighborhood Health to Heart (TNH2H), a large community-based participatory research (CBPR) initiative in Denver, Colorado, this article examines how food access can vary based on social advantage and disadvantage ( n  = 926). Findings uncovered important inequities and demonstrated a new and promising approach to understanding the food environment–health relationship.